NITROGEN IN COVERING IN THE SUNFLOWER CULTIVATION IN NOTILLAGE SYSTEM - BRUGINSKI, Denise Heimbecker (Scientia Agraria, 2000)
The present work, carried-out in the agricultural year of 1998/99, had as an objective to evaluate the effect of different levels of nitrogen in covering in the sunflower cultivation (Helianthus annuus L.) in no-tillage system. The experiment was driven in Fazenda Agripastos, in Palmeira, in the region of Campos Gerais in Paraná, in a red-yellow latossol, cultivated in no-tillage system since 1976. The experimental treatment used was the occasional blocks with four repetitions. The tested treatments were: doses of nitrogen (0, 25, 50, 75, 100 and 125 kg.ha-1, in the urea form, applied in covering when the plants were met in the V8 stage. The variety M734 was sowed in September, 1998. For the evaluations five plants were sampled in an, experimental unit in V8, V17, R1, R5.5 and R7 stages, to analyse the variables: total number of leaves, height of the plant, diameter of the stem, area to foliate, foliate area index, diameter of the capitulum and matter partition drought. During the crop some aspects were praised such as: grain yield, index of apparent crop, medium mass of l000 achene, achene number per capitulum, oil content in the achenes, number of bedridden plants, broken plants and plants with symptoms of rottenness of the capitulum, (Sclerotinia scleretiorum (Lib.) de Bary) it was accomplished some foliate analysis to obtain, the contents of N, P, K, Ca, Mg, Fe, Mn, Cu and Zn. The nitrogen fertilization in covering, in the conditions of the experiment, didnt present any increase In the grains. and any changing in its components, the achene oil content. the partition of dry matter and the morphologic characteristics on the sunflower. It was not proven the increase in the bedridden plants percentile, broken plants or with symptoms of rottenness of the chapter, even in the application of the largest doses of nitrogen. The N in covering o the sunflower cultivation under no-tillage system altered the contents on nitrogen in the leaves, but they didnt alter the contents of P, K, Ca, Mg, Fe, Mn, Cu and Zn.